Characteristics and outcomes of Italian patients from the observational, multicentre, hypopituitary control and complications study (HypoCCS) according to tertiles of growth hormone peak concentration following stimulation testing at study entry. (31st July 2015) - Losa, Marco; Beck‐Peccoz, Paolo; Aimaretti, Gianluca; Di Somma, Carolina; Ambrosio, Maria Rosaria; Ferone, Diego; Giampietro, Antonella; Corsello, Salvatore M.; Poggi, Maurizio; Scaroni, Carla; Jia, Nan; Mossetto, Gilberto; et al.
Summary Objective To determine whether characteristics and outcomes of Italian patients in the observational global Hypopituitary Control and Complication Study (HypoCCS) differed according to the degree of GH deficiency (GHD). Design Patients were grouped by tertiles of stimulated GH peak concentration at baseline (Group A lowest tertile, n = 342; Group B middle tertile, n = 345; Group C highest tertile, n = 338). Results Baseline demographics, lipid levels, body mass index categories and mean Framingham cardiovascular risk indexes were similar in the three groups and remained substantially unchanged over time, with no subsequent significant between‐group differences (except mean levels of triglycerides increased in the highest tertile group). GHD was adult‐onset for >75% of patients in all groups. The percentage of patients with multiple pituitary deficiencies was higher in Group A than in the other groups; isolated GHD was reported with highest frequency in Group C. Patients in Group A received the lowest mean starting dose of GH. Hyperlipidaemia at baseline was reported in 35·1%, 31·1% and 24·7% of patients in groups A, B and C, respectively (P = 0·029). Mean duration of GH treatment was 7·21, 5·45 and 4·96 years, respectively. The proportion of patients with adverse events did not differ significantly between groups, with a low prevalence over time of diabetes and cancer. Conclusions In Italian patients from HypoCCS, the level of GH deficit did not influence changes over time in metabolic parameters or adverse event profile, despite differences in GHD severity at baseline and in the starting GH dose.